Ergonomic factors and performance of academics in public universities in Nigeria - Osita, Fabian Chinedu; Chukwuemeka-Onuzulike, Nkechi Franciscan; Olayinka, Hammed Olalekan; Onyeizugbe, Chinedu Uzochukwu (goodwood publishing, 2024)
Purpose: This study investigated the effects of physical ergonomic factors on the performance of lecturers in public Universities in Anambra State, Nigeria. Research Methodology: This study adopted a descriptive survey design. The population of the study was 200; 187 questionnaires were returned and used in the analysis, and the census method was adopted. The source of the data was a questionnaire, which was tested for reliability using the split-half technique, and the value obtained was .998. Correlation analysis was carried out, and the hypothesis was tested at a 5% level of significance. Results: The findings indicated that there is a positive correlation between ergonomic factors and the performance of academics in the universities under study, and it was established that the coefficient level between ergonomic factors and the performance of academics is very high, and that the correlation coefficient is significant at the 0.01 levels (.000<0.01). Therefore, the null hypothesis was rejected and alternately accepted, which states that there is a significant relationship between physical ergonomic factors and the performance of academics in public Universities in Anambra State, Nigeria. Limitations: The narrowing of the scope of the study to only public Universities in Anambra State limits the generalizability of the study. Contribution: The Nigerian government will, by this study, know how to properly apply the physical ergonomic factors and its principles strictly adhered to, which will help reduce stress and work-related hazards in the workplace, leading to increased efficiency and stellar performance of public universities.